Comparative Discourse Analysis of Astronomical and Cosmological Words - Rustamova Feruzabonu Ilkhomovna; Shamsiddinova Mohitabon Shaxobiddinovna (Scientific Trends, 2024)
The article analyzes theoretical issues related to industry terms of modern astronomy and cosmology, lexical units, lexical conjugations, linguocultural features of words and phrases, as well as micro and macrosystems. The analysis focuses on identifying semantic shifts, pragmatic functions and discursive strategies used in the use of terminology related to astronomy and cosmology in various contexts (scientific publications, popular science literature, fiction, media, etc.). The study examines the evolution of the meaning of words, reflecting changes in the scientific understanding of the Universe, as well as the influence of social and cultural factors on the perception and use of astronomical and cosmological vocabulary.
Keywords: Discourse analysis, discourse, semiotics, context, astronomy, cosmology, red giant stars, white dwarf stars, yellow dwarf stars, brown dwarf stars, binary stars, supernovae, neutron stars, pulsar stars, quasar stars, blazar stars, black holes, nebula, dark matter, dark energy exoplanet.